Successful deployment and operational experience of using linear state estimator in wide‐area monitoring and situational awareness projects. Issue 18 (3rd July 2017) - Zhang, Lin; Chen, Heng; Martin, Kenneth; Faris, Anthony; Vutsinas, Megan; Bradberry, Tim; Phillips, Evan; Abu‐Jaradeh, Backer; Bui, Josh
Abstract : The US power industry has been pushing forward the adoption of synchrophasor technology for wide‐area monitoring and situational awareness. Many applications have been developed to take advantage of the GPS time‐stamped synchrophasor data. Linear state estimator (LSE) is one of the recent developments in the synchrophasor industry that has been gradually accepted and adopted by several US utilities under pilot projects. This study is aimed to provide the insights of successful deployments at the utility level, and to present key applications and business values of using LSE. One major contribution of this study is that the LSE has been enhanced to a production‐grade application for real‐time operation at control centre. The other major contribution of this study is to demonstrate the benefits and use cases of the LSE application based on first‐hand implementation and deployment experience at utilities. The LSE can (i) validate and condition phasor measurement unit data, (ii) provide an independent non‐iterative state estimator (SE) to complement the SE in Energy Management System for situational awareness, data analytics and grid resiliency and (iii) expand synchrophasor measurement observability for down‐stream synchrophasor applications. Several use cases are demonstrated in real time by pilot projects deployed at Bonneville Power Administration, Duke Energy, and Southern California Edison. LSE application's use cases and business values are presented to illustrate its successful deployment and operational experience in wide‐area monitoring and situational awareness system.